Hidden Inflammation: Pathophysiological Mechanisms, Clinical Implications, and Diagnostic Considerations—A Review - Ali Mohammed Sameen; Ibraheem Abdulnabi Shabeeb; Ahmed J. Alfahdaw (University of Thi-Qar Journal of agricultural research, 2025)
Inflammation is a part of the protective response of the body, however; it does not always manifest in an acute or obvious sense. In others immune activation may be chronic but subclinical. This state, sometimes called silent or low-grade inflammation, may be influencing your health over time. The inflammatory passion is not so violent, but still lasting and ever-burning is the metabolic equilibrium of body functions, vascular tone and cellular homeostasis. Low-level inflammation can be influenced by aging, obesity, metabolic stress and alterations in gut microbiota. These states can trigger natural immune-mediated pathways such as NF-κB signalling and inflammasome activation, resulting in a persistent release of pro-inflammatory molecules. Chronic exposure to this level of immune activation could also promote the onset or progression of chronic diseases – cardiovascular disease, T2D, cancer and neurodegenerative disorders. lignment=justify>One of the major challenges in the treatment of occult inflammation, has been that there have not specific diagnostic criteria. Conventional biomarkers such as C-reactive protein and interleukin-6 may act as surrogates of the burden of inflammation, but they fail to fully account for the intricacy of this aspect. Treatment primarily centres around lifestyle interventions, comprising of a balanced diet, exercise and maintaining an ideal body weight. In this way, subclinical inflammation could be a silent biological status that predisposes some individuals to chronic diseases. Additional study is required to enhance diagnosis and clarify its long-term clinical relevance.e